HEALTH FACULTY OF FORT DE KOCK UNIVERSITY BUKITTINGGI DIPLOMA III OF PHYSIOTHERAPY STUDY PROGRAM SCIENTIFIC PAPER - Reza Olyverdi; Tika Safitri (LPPM STIKES BHAKTI HUSADA BENGKULU, 2021)
Abstract : Urinary incontinence is the involuntary discharge of urine in sufficient quantity and frequency. It may cause the health and social problems. The purpose of this study was to determine The Effect of Kegel Exercise on the Intensity of Urinary Incontinence in the Elderly at Lubuk Basung Hospital. The type of this study was quantitative research with experimental pre-test-post-test research design. It was conducted at Lubuk Basung Hospital. The samples were chosen by purposive sampling. They were 15 elderly respondents.The average urinary incontinence in the elderly before giving kegel exercises was 10.07 with a standard deviation of 1.710 and after kegel exercises was 4.93 with a standard deviation of 2.815. By using t test with a mean different of 5.133 and p value = 0.005. It means that there was an effect of kegels exercise toward urinary incontinence in elderly at Lubuk Basung Hospital in 2021.It can be concluded that there was an effect of kegel exercise on the intensity of urinary incontinence in the elderly at Lubuk Basung Hospital before and after giving kegel exercise. For this reason, it is expected for the elderly to be able to perform movements or exercises at rest to reduce the intensity of urinary incontinence in order to improve the quality of life of the elderly. Keywords :Urinary Incontinence, Kegel Exercise